Black mixed-race men : transatlanticity, hybridity and 'post-racial' resilience - Joseph-Salisbury, Remi (Bingley, U.K. : Emerald Publishing Limited, 2018)
Whilst scholarship has increasingly moved to consider mixedness and the experiences of mixed-race people, there has been a notable lack of attention to the specific experiences of mixed-race men. This is despite growing recognition of the particular ways race and gender intersect. By centring the accounts of Black mixed-race men in the United Kingdom and United States, this book offers a timely intervention that extends the theoretical terrain of race and ethnicity scholarship and of studies of gender and masculinities. As it treads new and important ground, this book draws upon theories of performativity and hybridity in order to understand how Black mixed-race men constitute and reconstitute complex and multiplicitous identities. Post-racial conditions mean that Black mixed-race men engage in such processes in a context where the significance of race and racism is rendered invisible and denied. By introducing the theoretical concept of post-racial resilience, this study strives to capture and celebrate the contemporary, creative and innovative ways in which Black mixed-race men refuse the fragmentation and erasure of their identities. As it does so, the author offers a corrective to popular representations that have too readily pathologized Black mixed-race men. Focusing on the everyday through a discussion of Black mixed-race mens racial symbolism, experiences of racial microaggressions, and interactions with peers, "Black Mixed-Race Men: Transatlanticity, Hybridity and Post-Racial Resilience" offers an in-depth insight into a previously neglected area of scholarship.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Blacks -- Race identity; Racially mixed people -- Race identity; Ethnicity; Self-acceptance.; Social Science / Black Studies (Global).; Ethnic minorities & multicultural studies